A Role of Sphingosine in the Intracellular Survival of Neisseria gonorrhoeae - Solger, Franziska; Kunz, Tobias C.; Fink, Julian; Paprotka, Kerstin; Pfister, Pauline; Hagen, Franziska; Schumacher, Fabian; Kleuser, Burkhard; Seibel, Jürgen; Rudel, Thomas (Frontiers in Cellular and Infection Microbiology, 2020)
Obligate human pathogenic Neisseria gonorrhoeae are the second most frequent bacterial cause of sexually transmitted diseases. These bacteria invade different mucosal tissues and occasionally disseminate into the bloodstream. Invasion into epithelial cells requires the activation of host cell receptors by the formation of ceramide-rich platforms. Here, we investigated the role of sphingosine in the invasion and intracellular survival of gonococci. Sphingosine exhibited an anti-gonococcal activity in vitro. We used specific sphingosine analogs and click chemistry to visualize sphingosine in infected cells. Sphingosine localized to the membrane of intracellular gonococci. Inhibitor studies and the application of a sphingosine derivative indicated that increased sphingosine levels reduced the intracellular survival of gonococci. We demonstrate here, that sphingosine can target intracellular bacteria and may therefore exert a direct bactericidal effect inside cells.